Knowledge and Practices of Perineal Wound Care among Post Partum Women during COVID19 Pandemic - Shinta Novelia; Rosmawati Lubis; Erma Sulistiyorini (Nursing and Health Sciences Journal (NHSJ), 2021)
Background: Perineum wound care is one of the factors to prevent infection during the puerperium. Because the perineum is a difficult area to keep dry and clean. Care and observation are needed during the puerperium to ensure that the perineum is healed by taking care of the perineum properly and correctly. During the Covid-19 pandemic, postpartum maternal visits to health facilities were very limited because it was to avoid transmitting infectious diseases to postpartum mothers. Objective: To determine the knowledge of the post-partum women about the practice of perineal wounds during the Covid-19 pandemic at the Banjar Health Centre in 2021. Methodology: this descriptive study used a cross sectional approach. The sample in this study was 102 respondents with accidental sampling technique. Data were analyzed using SPSS with Chi Square, which previously tested the validity and reliability. Results: The practice of treating perineum wounds in the working area of the Banjar Health Centre obtained an average score of 73.5. Based on the knowledge obtained an average value of 89.2. The results of the Chi Square test showed that all independent variables had a relationship with perineum wound care practices, including knowledge (p = 0.001). Conclusions and Suggestions: The practice of perineum wounds care in postpartum women has a relationship with the women’s level of knowledge. Postpartum women can expand their knowledge about wound care in the perineum during the puerperium through mass and electronic media and counseling provided by health personnel.